Air Mensucikan Dan Menajiskan Pada Naskah Muqaddimah Imam Bafadal Al-Hadramy Karya Al-Haitami (Tinjauan Filologi) - Muhammad Dedad Bisaraguna Akastangga (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2020)
Syarah Muqoddimah Al-Imam Bafadal Al-Hadrami By Al-Haitami is a single manuscript, this manuscript is kept neatly in the Al-Imdad Islamic Boarding School Bantul Yogyakarta. Chapter Purifying water and polluting water are the main focus of this research. The problem in this study is to find out the sound of the text of the manuscript and the content or discourse of the text, as well as to apply the hadith in the text of the manuscript with J.E. Gracia's Hermeneutic theory about the interpretation function theory. Which he divided into three parts, namely historical function, meaning function and implicative function. The method used in this study is the diplomatic method of rewriting the contents of the text without any addition or subtraction, but this method does not help the reader in understanding the contents of the text. Then the researcher also uses a critical or standard method that is by rewriting the contents of the text accompanied by improvements to the text limited to errors in writing. All of these improvements, if any, will be done by making notes so that the text is maintained its authenticity. The results of the analysis starting from text editing, transliteration, translation up to the analysis stage of the contents of the text of the manuscript, it can be concluded that the manuscript is a manuscript which generally contains the book of fiqh with various discussions. In this case, as in the study of the mandatory water and polluting water, a comprehensive understanding of various non-defiling water can be used for purification, as written in the text of the text there are three main topics, namely water, amounting to two qullah , the water licked by the cat and the water from the bath does not cause the water to become unclean. Whereas in terms of content analysis found asbabul wurud from the hadith that discusses these three things from various narrators, in Gracia interpretation theory is called the historical function, and also obtained the meaning function of the hadith to always maintain impurity, and in terms of the implicative function obtained implications to modern life today to be more careful in purification.Â Â